Conditional probability of the daily minimum temperature in certain types of circulation on a seasonal basis in the Zywiec Valley in Southern Poland - Szczotka, Paulina (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2017)
Air minimum temperature is very important for the natural environment and human activity. This paper presents certain aspects related to the variability of daily minimum temperature of air in the winter (XII, I, II) in the Zywiec Valley, in relation to the synoptic situation in the valley. The analysis is based on the results of research carried out at one point node (the grid) obtained from the base Carpat Clim database. The node is located at the bottom of the Zywiec Valley in the period 1961-2010. The study was complemented with a comprehensive analysis of local conditions for atmospheric circulation and temporal variability over a 50 years period. For this purpose, the classification of types of atmospheric circulation (Niedźwiedź 1981) was used for the upper Vistula river basin. Extreme temperatures included an average minimum temperature of air exceeding the 90th and 95th percentile. The relationship between the extremes of air temperature and atmospheric circulation types was examined by analyzing the frequency of occurrence of extreme values and their conditional occurrence in each particular type of atmospheric circulation.